Changes and continuities over time in the cultural significance of the Nyaminyami water spirit among the BaTonga people of northwestern Zimbabwe - Matanzima, Joshua (Rhodes University, Faculty of Humanities, Department of Anthropology, 2019)
Research attests that beliefs in water spirits are an integral part of cultures of many indigenous communities across the globe. These water spirits play significant political, religious and socio-economic roles for the people concerned. However, the functions of water spirits are not constant, but change over time, especially when the people believing in water spirits undergo drastic socio- economic processes of change. It is in this context that this thesis traces the cultural significance over time, of the Nyaminyami water spirit, among some BaTonga people, living in the immediate vicinity of the Kariba gorge area, in north-western Zimbabwe. While previous studies document the existence of beliefs in Nyaminyami, none of these has systematically traced the historical significance of Nyaminyami, in terms of changes and continuities over time. Thus, this thesis makes a valuable contribution to knowledge with regards to the history and religion of the BaTonga people. The thesis argues that Nyaminyami's cultural significance or functions evolved over time, due to numerous socio- economic and political processes of change. The major changes that significantly influenced the practices relating to Nyaminyami include colonialism, Kariba dam construction and resettlement, the migration after resettlement in the 1960s and 1970s, the independence of Zimbabwe, and the alienation of the Kariba waterscape from the BaTonga. To be able to arrive at specific findings and conclusions, the thesis is underpinned by theories about resettlement, approaches to water divinities, and theories of religion and social change. The thesis has five ethnographic chapters that focus on specific time periods, illustrating the major socio- economic changes of each epoch, and showing how these changes impacted upon practices and beliefs relating to Nyaminyami. The thesis also documents how Nyaminyami beliefs are variedly distributed along different social variables that include gender, age, income and geographical location. In order to achieve the findings presented, the thesis utilized ethnographic evidence obtained from semi- structured interviews, participant observation, anthropology of extraordinary experience, document review and archival research.
Keywords: Water spirits -- Zimbabwe; Tsonga (African people) -- Zimbabwe; Tsonga (African people) -- Zimbabwe -- Religion; Tsonga (African people) -- Zimbabwe -- Rites and ceremonies; Tsonga (African people) -- Zimbabwe -- Social life and customs; Mythology, Tsonga; Mythology, Zimbabwean; Nyaminyami (Spirit)